When Do Companies Need a Board-Level Risk Management Committee? - Choi, Ivan (International Finance Corporation, Washington, DC, 2014)
Risk management is nothing new. But the global financial crisis and corporate failures in recent years have put risk management in the spotlight. Who is ultimately responsible for it? Responsibility for risk management should start in the boardroom, as the board is ultimately responsible for the organization's decision making, business performance, and value creation, all of which are associated with risk. The chief executive officer, who is accountable to the board, has the responsibility to ensure proper execution of the risk-management strategy and policies laid down by the board. The board governs while management manages. The board's risk management role should therefore be the governance of risk overseeing, directing, and setting policies and monitoring performance.